Reconstructing Sustainable Development Through Zakat: A Maqasid Al Shariah Framework for SDGs Integration: - Ahmad Fuatul Hasan; Tanzilla Nur Yufikha; Nafisah Amalia Azzahra; Kayode Muhammed Ibrahim; Khusnul Khatimah (NALAR FIQH: Jurnal Hukum Islam, 2026)
This article examines the integration of zakat and the Sustainable Development Goals (SDGs) through the framework of maqasid al-shariah within the broader discourse of Islamic sustainable development. Existing studies predominantly conceptualize zakat as a technical instrument for poverty alleviation and wealth redistribution, while limited attention has been devoted to its epistemological and philosophical integration with contemporary sustainable development paradigms. This study aims to analyze the substantive relevance of zakat to the SDGs, explore maqasid al-shariah as a normative foundation for sustainable welfare, and formulate an integrative model of maqasid-based sustainable development. Employing normative juridical research with a qualitative library approach, this study critically examines contemporary literature on Islamic social finance, sustainable development, and maqasid studies. The findings reveal that zakat demonstrates substantial relevance to several SDGs, particularly those related to poverty reduction, social justice, economic inclusion, and sustainable welfare. Moreover, maqasid al-shariah offers a comprehensive ethical and philosophical framework capable of reconstructing sustainable development beyond material growth toward a justice-oriented and human-centered paradigm of welfare. Based on these findings, the study proposes a "Maqasid-Based Sustainable Zakat Development Model" that integrates zakat governance, productive empowerment, Islamic social finance, and SDGs-oriented development strategies. The article contributes to the discourse on Islamic economic law and sustainable development by providing an integrative framework that bridges Islamic normative principles with contemporary global development agendas.